2017
DOI: 10.3390/agronomy7020038
|View full text |Cite
|
Sign up to set email alerts
|

Spore Density of Arbuscular Mycorrhizal Fungi is Fostered by Six Years of a No-Till System and is Correlated with Environmental Parameters in a Silty Loam Soil

Abstract: Arbuscular mycorrhizal fungi (AMF) play major roles in nutrient acquisition by crops and are key actors of agroecosystems productivity. However, agricultural practices can have deleterious effects on plant-fungi symbiosis establishment in soils, thus inhibiting its potential benefits on plant growth and development. Therefore, we have studied the impact of different soil management techniques, including conventional moldboard ploughing and no-till under an optimal nitrogen (N) fertilization regime and in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
(51 reference statements)
2
3
0
1
Order By: Relevance
“…Therefore, with such a small amount taken for testing in the sequencing of the ITS variable region for fungi in the NGS method, it could happen that this material has not been amplified. Similar results in AMF spores were obtained by authors of other papers [46][47][48]. Therefore, the results obtained by us are all the more valuable because both a modern research method (NGS in paper Grz ądziel and Gał ązka [11]) and traditional methods of counting AMF spores were used in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, with such a small amount taken for testing in the sequencing of the ITS variable region for fungi in the NGS method, it could happen that this material has not been amplified. Similar results in AMF spores were obtained by authors of other papers [46][47][48]. Therefore, the results obtained by us are all the more valuable because both a modern research method (NGS in paper Grz ądziel and Gał ązka [11]) and traditional methods of counting AMF spores were used in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The correlation with organic C, total-N, C/N ratio, and total-K is positively insignificant (Table 4). Several studies also reported an insignificant relationship between total AMF spore density with soil pH, organic C, total-N, C/N ratio (Sivakumar, 2013;Verzeaux et al, 2017). Wang et al (2015) reported the relationship between AMF spore density and total-P soil was insignificant, whereas in this study a positive significant correlation was found (r 2 = 0.74) at the p < 0.05 level (Table 4).…”
Section: Discussionsupporting
confidence: 40%
“…Residual, organic material present in the soil was also able to increase hyphal growth, independently of the host plant, which probably explains why in the absence of tillage and of N fertilization, AMF development was improved [17] as well as fungal spore density [105].…”
mentioning
confidence: 99%